DEFICIÊNCIA VISUAL E EDUCAÇÃO CIENTÍFICA:ORIENTAÇÕES DIDÁTICAS COM UM APORTE NA NEUROCIÊNCIA COGNITIVA E TEORIA DOS CAMPOS CONCEITUAIS - Eder Pires de Camargo; Edval Rodrigues de Viveros (Universidad Distrital Francisco José de Caldas, 2011)
The aim of this paper is to present an educational proposal with didactic and pedagogical orientations, to the Science Education for people with visual impairments. Then, we use as main reference, Gérard Vergnaud's Theory of Conceptual Fields, joining with a translational focus, applying empirical results of Cognitive Neuroscience. Within this, we highlight the role of educational activities related with 'multisensory scientific literacy ', focusing on the linguistic triad: read, interpretation and textual representation. We hope this perspective, become in the future an important component on guidelines for composing a 'semiotic protocol' for Science Education. Realizing too, epistemological peculiarities, pedagogic and didactic specificities in this area, and, revealing such properties on the cognitive constructs, for science and technology education.